The Power of Proving the Testimony of a Child Without Being Sworn in Proving the Indictment of the Crime of Child Intercourse - Siti Chusnul Nurlaela; Boy Nurdin (Rechtsnormen: Journal of Law, 2024)
Background: The testimony of children in criminal cases, particularly in cases of child intercourse, often presents significant challenges in Indonesia’s legal system. The issue arises when children provide testimonies without being sworn in, raising questions about their evidentiary value. Despite existing legal provisions, the criminal justice system faces difficulties in balancing the protection of children’s rights and ensuring the credibility of their testimonies. Objectives: This study aims to analyze the evidentiary power of child testimony without an oath in proving the indictment of child intercourse crimes. It seeks to identify gaps in regulation and implementation and provide recommendations for improving judicial practices. Methods: The study employs a qualitative approach, analyzing Indonesian legal provisions, case studies, and international comparisons. Data were collected from legal documents, court rulings, and interviews with legal practitioners. Research Findings: The findings indicate inconsistencies in judicial practices regarding child testimony. Factors influencing the credibility assessment include the child’s age, consistency of statements, and supporting evidence. The study highlights a disconnect between legal frameworks and their practical application. Conclusion: The study concludes that legal reform, enhanced capacity building for law enforcement, and a multidisciplinary approach are crucial for improving the handling of child testimonies. These measures can strengthen the criminal justice system while safeguarding children’s rights.